Commentaries on "The Lenses of Lean". Issue 5 (17th May 2021) - Cusumano, Michael A.; Holweg, Matthias; Howell, Josh; Netland, Torbjørn; Shah, Rachna; Shook, John; Ward, Peter; Womack, James
Abstract: The phenomenon of the Toyota Production System (TPS) and the term "Lean" have received much attention from researchers and especially practitioners over the past 40 years. As scholarly perspectives on these topics continue to evolve, we invited Wally Hopp and Mark Spearman to contribute an essay to the JOM Forum that became "The Lenses of Lean, " and we invited several other prominent authors affiliated with Lean to react to that article and share their perspectives on Lean. We are delighted to have received four such contributions, which we have assembled here with the hope of furthering this important conversation (Note: For consistency of exposition, we have capitalized the term "Lean" throughout these commentaries when it is used in the phenomenological sense). —Tyson Browning and Suzanne de Treville